The SGLT-2 Inhibitors and their Role in the Treatment of Heart Failure - A Review of Literature - Ciraolo, Silvia; Agnieszka Kulczycka-Rowicka,; Wojda, Joanna; Lesiczka-Fedoryj, Katarzyna; Walczak, Anna; Kościuszko, Zuzanna; Sobiński, Adam; Czerwonka, Matylda; Kurza, Katarzyna; Podolec, Julianna (Quality in Sport, 2025)
The purpose of research: Heart failure (HF) is an important global health concern. Despite advancements in treatment, HF remains the leading cause of hospitalization among the elderly. The development of sodium-glucose cotransporter 2 (SGLT2) inhibitors has shown promising cardiovascular and renal benefits beyond glucose control. This study aims to explore the potential mechanisms by which SGLT2 inhibitors provide cardiovascular protection, regardless of type 2 diabetes mellitus (T2DM). Research materials and methods: A comprehensive literature review was conducted, analyzing clinical trials, guideline documents, and mechanistic studies on SGLT2 inhibitors. Definitions and classifications of HF, risk factors, and cardiovascular effects of SGLT2 inhibitors were reviewed. Key studies such as EMPA-REG OUTCOME, DAPA-HF, and others were analyzed to identify mechanisms contributing to cardiovascular protection. Results: SGLT2 inhibitors provide cardiovascular benefits in HF patients, regardless of T2DM status. Key mechanisms include natriuresis, improved cardiac metabolism, reduced inflammation, prevention of cardiac remodeling, sympathetic inhibition, enhanced vascular health, and better kidney function. Conclusions: The benefits of SGLT2 inhibitors extend beyond glucose control. They provide various effects, including improved hemodynamics, reduced inflammation, and enhanced cardiac energy metabolism. While several mechanisms have been proposed, further research is necessary to rule which are most critical. The benefits observed with SGLT2 inhibitors stress their potential as a cornerstone in HF management, regardless of a patient’s diabetes status.